Efektivitas Bimbingan Belajar Informal Tetap Muka Siswa Kelas VI Pasca Pandemi Covid-19 - Rahman, Adiputra; Salmawati Salmawati (Jurnal Bintang Pendidikan Indonesia, 2024)
The rapid development of the times and technology today has given rise to many innovations and conveniences, including in the field of education for students and teaching staff. Learning methods are no longer conventional or face-to-face in the classroom, but through online-based devices the teaching and learning process can still run, especially when the Covid 19 pandemic hit. Mamuju Regency, West Sulawesi Province, in the education sector, especially at primary school level or equivalent, there are 310 schools including state schools and private schools. In general, interest in informal education, one of which is tutoring, is still low. This journal presents data and results of mathematics learning assessments at the Ranu Prima College Tutoring Institute, Mamuju branch. The aim of presenting this data is to determine the effectiveness of tutoring in the post-pandemic period and its existence in the future. The results obtained from this activity show that the offline/face-to-face tutoring system is still more effective than the online learning system. This is proven by assessments by parents/guardians of students and students' enthusiasm for the existence of tutoring even though the duration of implementation is relatively short. Of the total of 30 participants, 25 participants remained until the program was completed, providing feedback in the assessment and assessing that the tutoring was effective in equipping students to prepare the final school exams.